EFEKTIFITAS BREAST CARE TERHADAP PRODUKSI ASI DI KOTA PEKANBARU - Ade Febriani; Erick Caesarrani (JOMIS (Journal of Midwifery Science), 2023)
Breastfeeding is the best investment for survival and improving the health, social, economic development of individuals and nations. Post partum breast care is breast care for mothers after giving birth as early as possible. The benefits of post partum breast care include launching the milk expulsion reflex or let down reflex, effective ways to increase the volume of expressed breast milk, and preventing dams in the breasts/swollen breasts. The purpose of this study was to determine the effectiveness of Breastcare in breastfeeding mothers on milk production.This type of research is quantitative with a quacy experimental research design with a two group pretest-posttest design where this design measures the amount of breast milk that is massaged with those who are not massaged (pretest) and reassessed after the massage (pretest). This research will be conducted in the Work Area of ​​the Rumbai Health Center. The time of the study was carried out from February to June 2022. . the sample group to be taken is 11 people with a total of 22 people. The study was conducted for 7 days by giving breastcare for 7 times and then the milk production was seen on the 8th day. The results of data analysis using independent t test in table 6 above show that the average milk production in the postpartum breast care group is smoother than the group without postpartum breast care, namely 6.84 > 3.72 and the thit value > ttab (16.47 > 1.691) or the value of : 0.000 <0.05, which means that Postpartum Breastcare is effective in increasing breast milk production in breastfeeding mothers. Breastcare can be used as a recommendation as an addition to routine care for postpartum and breastfeeding mothers to help succeed in exclusive breastfeeding.